Anakinra authorized to treat severe coronavirus disease 2019; Sepsis breakthrough or time to reflect? - Shapiro, Leland; Scherger, Sias; Franco-Paredes, Carlos; Gharamti, Amal; Henao-Martinez, Andrés F. (Frontiers in Microbiology, 2023)
Insanity is doing the same thing over and over and expecting different results"-often attributed to Albert EinsteinThe anti-inflammatory drug anakinra blocks effects of the inflammatory cytokine interleukin-1.A recent study (SAVE-MORE) showed positive results using anakinra to treat Coronavirus Disease 2019 . Subsequently, use of anakinra was approved to treat COVID-19 in Europe and vetted for emergency use in the United States. We believe enthusiasm for using this drug as a COVID-19 treatment should be reconsidered. The SAVE-MORE study was conducted in a way that makes applicability to patient care challenging. Moreover, use of anakinra to treat COVID-19 relies on a defective concept, namely the idea that hyperinflammation or cytokine storm causes organ malfunction or death due to COVID-19. The cytokine storm concept is based on notions that are confusing and imprecise, is supported by weak scientific evidence, and therapies based on this concept have failed more than 100 times in clinical studies. It appears interest in treating COVID-19 with anakinra is the latest example of a frustrating cycle where these kinds of drugs attain initial credibility that subsequently evaporates. Since there is every reason to believe these cycles will continue, we need to explain why these cycles occur and use this understanding to radically change our approach to treating serious infections.